Trait‐habitat associations explain novel bird assemblages mixing native and alien species across New Zealand landscapes. (9th November 2021) - Barnagaud, Jean‐Yves; Brockerhoff, Eckehard G.; Mossion, Raphaël; Dufour, Paul; Pavoine, Sandrine; Deconchat, Marc; Barbaro, Luc
Abstract: Aim: Species introductions have reshaped island faunas for the last 200 years, often threatening native biodiversity. Approximately equal numbers of native and alien species currently co‐occur in the New Zealand avifauna, but they show distinct habitat use. Antagonistic interactions, habitat affinities and legacies of introduction history may concur to explain their segregation along habitat gradients. To investigate these processes, we explored how habitat, ecological traits and introduction history relate with the current composition of bird assemblages. Location: New Zealand Taxon: Birds Methods: We analysed 917 bird point counts spread along habitat and elevation gradients in the Canterbury region, South Island and related 10 ecological traits to landscape composition using a three‐table ordination method known as "RLQ analysis", accounting for spatial autocorrelation and phylogeny. We tested whether alien species' positions in the RLQ were related to proxies of introduction history. Results: Eighteen endemic, 11 native and 19 alien species were distributed along a gradient from forest to open‐habitat assemblages, in relation to foraging mode, nesting site and body size. A second gradient segregated species between native and exotic forests according to territoriality, sedentarity and diet. Traits accounted for the separation of native and alien bird species in forests, but not in open habitats. Phylogenetic signals emerged from the separation of native and alien species by forest type, and spatial structures suggested a landscape‐level, rather than regional or local determinism. These correlations were independent of introduction history, although open‐habitat assemblages tended to host alien species introduced later in time. Main conclusions: Habitat type and resource availability explain the spatial partitioning of New Zealand bird assemblages between native and alien species more consistently than competitive exclusion. We conclude that trait‐mediated ecological differences among species have likely played a predominant role in species' segregation among landscapes, while maintaining endemic bird assemblages in native forests.